Guerillas; A History and Analysis - Campbell, Arthur (London Arthur Barker Limited, 1967)
Guerrilla warfare is the warfare of today. It is either resorted to by the weak because circumstances prevent them from deploying regular armed forces, or adopted by the strong to enable them to achieve political aims without the terrifying risks, imposed by nuclear weapons, of all-out warfare. This is the first book to cover the whole development of modern guerrilla warfare from its inception in Spain in 1808 to the time of writing. Lt. Col. Arthur Campbell, who was himself engaged against guerrillas in three widely different campaigns, takes the major guerrilla wars of the nineteenth and twentieth centuries and treats them one by one. His separate accounts are linked by a series of narratives which keep the reader abreast with the various developments of this form of fighting. Many of the stories are told in the first person as if by a participant, others are given more objective treatment, but each is a gripping account of courage and cruelty, of barbarity and bravery, and of extreme endeavor. By his treatment Arthur Campbell has covered every aspect of guerrilla fighting, from the theories and practices of such eminent authorities as Marx and Mao to the individual actions and emotions of men and women engaged on the battlefields, either as guerrillas or counter-guerrillas. The effect on participants of both national and international politics is clearly shown, as is the vital importance of the approach to people's hearts and minds. In his closing chapters the author draws conclusions from the past. These chapters in effect summarize the essential ingredients of success in both guerrilla and counter-guerrilla warfare.--Adaptd frmo book jacket.
Include Bibliography and Index
Keywords: Guerrillas